Hubungan Indeks ROX dengan Mortalitas Pasien COVID-19 di RSUP Dr. Sardjito - Naomi, Diah Anis; Wisudarti, Calcarina Fitriani Retno; Widodo, Untung (Jurnal Komplikasi Anestesi, 2022)
Background: In December 2019, a new infectious disease caused by a corona virus named SARS-CoV-2 emerged. COVID-19 disease causes multi-organ failure that occurs in the lungs and extra-pulmonary, sepsis, and even death. Pulmonary disorders that often occur in COVID-19 patients are ARDS. Early recognition of ARDS can be done by assessing the clinical condition of the patient and the parameters of RR and SpO2. ROX is a calculation of Index (SpO2/FiO2)/RR. The ROX index may be one of the predictors of mortality in COVID-19 patients. Methods: An observational study with a retrospective cohort approach to COVID19 patients who were hospitalized at Sardjito General Hospital in July 2020 to June 2021. Patients with COVID-19 without oxygen therapy or with nasal cannula oxygen therapy, NRM, or HFNC who were hospitalized, the ROX Index were calculated on the first day of treatment and then assessed for patient mortality and length of stay. The data was taken from medical records at the Medical Records Installation at Sardjito General Hospital. Results: There were 953 research subjects with average age of 51 (± 15.5) years old, 479 women (50.3%) and 474 men (49.7%). There was a significant relationship between the ROX index 15.06 and the mortality of COVID-19 patients (p < 0.001, HR = 2.15, 95% CI 1.57-2.94). Other factors related to mortality in COVID-19 patients were age, oxygen therapy with HFNC, hypertension, diabetes mellitus, chronic kidney failure, and cardiovascular disease. The survival time of subjects with an ROX index of 15.06 was 24 days, shorter than the index group > 15.06, which was 31 days (p < 0.001). The ROX index did not have a significant relationship with the length of stay in the hospital. The average length of stay in the ROX 15.06 index group was 17 days, longer than the > 15.06 index group, which was 14 days (p=0.002). Factors related to length of stay were age ³ 65 years, history of hypertension and diabetes mellitus. Conclusion: There was a significant association of ROX index and mortality of COVID-19 patients at Sardjito General Hospital.